Characterization and subtyping of Cronobacter spp. from imported powdered infant formulae in Argentina - Terragno, R. (2009)
Fil: Terragno, R. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas; Argentina.